LOCAL WISDOM-BASED EDUCATION IN BUILDING THE PROFILE OF PANCASILA STUDENTS IN ELEMENTARY SCHOOLS: A CRITICAL ANALYSIS FROM A PHILOSOPHICAL-PEDAGOGICAL PERSPECTIVE - Dede Ginanjar; Yusuf Tri Herlambang; Ai Sutini (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Local wisdom-based education plays an important role in shaping the character of elementary school students, particularly in developing the Pancasila Student Profile in line with the Merdeka Curriculum. This study aims to examine the contribution of local wisdom to the main values of the Pancasila Student Profile through a philosophical-pedagogical approach. The method used is Systematic Literature Review (SLR) by analyzing scientific articles published from 2020 to 2025. The SLR process includes identification, screening, quality assessment, and synthesis of 30 relevant articles. The results show that the integration of local wisdom through traditional arts, cultural practices, and ethnopedagogical knowledge consistently strengthens the dimensions of the Pancasila Student Profile, such as global diversity, mutual cooperation, independence, creativity, and responsibility. Local culture-based learning also increases learning motivation, students' emotional attachment to the social environment, and the formation of cultural identity. Philosophically, local wisdom is a source of values that fosters ethical awareness; pedagogically, it provides contextual and meaningful learning. In conclusion, education based on local wisdom contributes significantly to the formation of the Pancasila Student Profile in elementary schools. Strengthening its implementation is necessary through curriculum development, innovative learning models, and community cultural support.